The preparation of activated carbons from chips of oil palm trunk catalysed by ZnCl2/CO2: Surface area and porosity studies - Hussein, Mohd Zobir; Zainal, Zulkarnian; Ibrahim, Ramli; Kheong, Kohr K.; Muhammad, Badri (Wiley, 1995)
Activated carbons were prepared by ZnCl2/CO2 activation of the chips of oil trunk. The surface area and the nature of the porosity of the resulting activated carbons were found to be related to the concentration of the impergnated zinc solution to the precursor. It is possible to prepare activated carbons with a fairly high surface area (more than 2000 m2 g−1) from chips of oil palm trunk.